2019
DOI: 10.2217/fon-2019-0258
|View full text |Cite
|
Sign up to set email alerts
|

The NEOLETEXE Trial: A Neoadjuvant Cross-Over Study Exploring the Lack of Cross Resistance Between Aromatase Inhibitors

Abstract: The aromatase inhibitor letrozole (Femar®/Femara®) and the aromatase inactivator exemestane (Aromasin®) differ in their biochemical effect on the aromatase enzyme. Letrozole is a competitive aromatase inhibitor while exemestane binds irreversibly to the aromatase enzyme. This pharmacological difference is of clinical interest since a lack of cross-resistance has been documented. It has been demonstrated in several clinical trials that exemestane may cause a disease regression following resistance to nonsteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…From February 2015 to November 2019, patients with biopsy-proven locally advanced oestrogen receptor (ER)positive breast cancer and human epidermal growth factor receptor 2 (HER-2)-negative status suitable for NET were eligible for this prospective, open-label, randomized sub-study of the Neoletexe trial, (Fig. 1) [36]. All participants had to be postmenopausal to benefit from aromatase inhibition.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…From February 2015 to November 2019, patients with biopsy-proven locally advanced oestrogen receptor (ER)positive breast cancer and human epidermal growth factor receptor 2 (HER-2)-negative status suitable for NET were eligible for this prospective, open-label, randomized sub-study of the Neoletexe trial, (Fig. 1) [36]. All participants had to be postmenopausal to benefit from aromatase inhibition.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…5 (Fig. 1) [36]. Calliper measurements of maximum tumour size (in centimetres) and tumour quadrant location were recorded.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Our prospective, randomized, open-label, cross-over substudy from the NEOLETEXE trial enrolled 71 participants with histologically confirmed unilateral strongly ER + , human epidermal growth factor receptor 2 (HER2)-negative LABC between February 2015 and December 2020 at Akershus University Hospital (Fig. 3 ) [ 24 ]. The 50 eligible participants had to be postmenopausal to benefit from neoadjuvant aromatase inhibitors (NAAI) with no or limited distant metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…1) is a neoadjuvant, randomized, open-label, intra-patient, cross-over trial with the intention to study the effects of sequential aromatase inhibition by type-I aromatase inhibitor letrozole and type-II aromatase inactivator exemestane in a randomized, intra-patient cross-over fashion in vivo. The trial has been approved by the Regional Ethics Committee of South-East Norway (project number 2015/84) [20]. In this particular sub-study, a total of 39 postmenopausal women, all diagnosed with locally advanced, ER-positive and HER-2 negative primary cancer were included (Table 1).…”
Section: Trial Design and Patientsmentioning
confidence: 99%
“…However, the precise explanation for the observed lack of cross-resistance between steroidal and nonsteroidal aromatase inhibitors is still unknown and it has been suggested that a detailed understanding of this clinical phenomenon may potentially provide a new strategy to treat hormone-sensitive breast cancer [18,19]. To investigate the fundamental differences in the effects caused by non-steroidal AIs and steroidal AIs in vivo, we designed the NEOLETEXE-trial [20]; (Figure 1). The present manuscript reports the results of a planned cytokine-substudy of the NEOLETEXE-trial.…”
Section: Introductionmentioning
confidence: 99%